Survey of Corporate Governance Practice in the Kyrgyz Republic - International Finance Corporation (International Finance Corporation, Bishkek, 2017)
The International Finance Corporation (IFC), a member of the World Bank Group is the biggest global development institute focusing its activities on the private sector in developing and transition economies. The IFC creates opportunities for improving the quality of life and reducing poverty. The IFC Corporate Governance Project was launched in 2008 to assist joint stock companies (JSC ) in the Kyrgyz Republic to improve their corporate governance, as well as to strengthen capacity of JSC s for attracting investment. This project is the result of a logical extension of the IFC Corporate Governance Program in Central Asia launched in Kazakhstan in 2006 and in Tajikistan in 2007. The project aims to improve corporate governance practices in JSC s including banks. As part of the project, the project team works to involve in governmental working groups in legislative and enforcement reform in the area of corporate governance in the Kyrgyz Republic. To raise awareness of the population on issues relating to corporate governance, the project conducts the campaigns to inform the wider public of the latest trends in improving corporate governance practices. This IFC Central Asia Corporate Governance Project is supported by the Netherlands-IFC Partnership Program.